Organized Aggregation of Porphyrins in Lipid Bilayers for Third Harmonic Generation Microscopy. (29th September 2015) - Cui, Liyang; Tokarz, Danielle; Cisek, Richard; Ng, Kenneth K.; Wang, Fan; Chen, Juan; Barzda, Virginijus; Zheng, Gang
Abstract: Nonlinear optical microscopy has become a powerful tool for high‐resolution imaging of cellular and subcellular composition, morphology, and interactions because of its high spatial resolution, deep penetration, and low photo‐damage to tissue. Developing specific harmonic probes is essential for exploiting nonlinear microscopic imaging for biomedical applications. We report an organized aggregate of porphyrins (OAP) that formed within lipidic nanoparticles showing fingerprint spectroscopic properties, structure‐associated second harmonic generation, and superradiant third harmonic generation. The OAP facilitated harmonic microscopic imaging of living cells with significantly enhanced contrast. The structure‐dependent switch between harmonic (OAP‐intact) and fluorescence (OAP‐disrupted) generation enabled real‐time multi‐modality imaging of the cellular fate of nanoparticles. Robustly produced under various conditions and easily incorporated into pre‐formed lipid nanovesicles, OAP provides a biocompatible nanoplatform for harmonic imaging. Abstract : Aufbau und Charakterisierung eines organisierten Porphyrin‐Aggregats (OAP) in Lipid‐Nanopartikeln für die nichtlinear‐optische Mikroskopie werden beschrieben. Der strukturabhängige Wechsel des Photoverahltens des Aggregats zwischen Oberton‐ (OAP intakt) und Fluoreszenz‐Erzeugung (OAP gespalten) ermöglicht die Verfolgung von Nanopartikeln in lebenden Zellen. Grüne Stäbchen: Porphyrinaggregate.